2020
DOI: 10.1371/journal.pgen.1009125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H2A.Z deletion is rescued by compensatory mutations in Fusarium graminearum

Abstract: Fusarium head blight is a destructive disease of grains resulting in reduced yields and contamination of grains with mycotoxins worldwide; Fusarium graminearum is its major causal agent. Chromatin structure changes play key roles in regulating mycotoxin biosynthesis in filamentous fungi. Using a split-marker approach in three F. graminearum strains INRA156, INRA349 and INRA812 (PH-1), we knocked out the gene encoding H2A.Z, a ubiquitous histone variant reported to be involved in a diverse range of biological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 122 publications
(199 reference statements)
3
12
0
Order By: Relevance
“…Like the Fgprp4 , fng1 , and a few other F. graminearum mutants with severe growth defects [ 42 , 56 , 57 , 58 ], the Fgyck1 mutant produced spontaneous suppressors with faster growth rates. By whole genome sequencing of seven selected suppressors, we identified mutations in seven predicted genes, including orthologs of yeast BNI4 , TNA1 , MIG1 , and MSS4 .…”
Section: Discussionmentioning
confidence: 99%
“…Like the Fgprp4 , fng1 , and a few other F. graminearum mutants with severe growth defects [ 42 , 56 , 57 , 58 ], the Fgyck1 mutant produced spontaneous suppressors with faster growth rates. By whole genome sequencing of seven selected suppressors, we identified mutations in seven predicted genes, including orthologs of yeast BNI4 , TNA1 , MIG1 , and MSS4 .…”
Section: Discussionmentioning
confidence: 99%
“…H2A.Z has been linked to a wide variety of different sometimes contradictory nuclear functions, including transcriptional activation, transcriptional repression, RNA Polymerase II elongation, heterochromatin, anti-silencing, cell-cycle control, DNA replication, DNA damage repair, chromosome segregation, and genome integrity (Chen and Ponts 2020 ). The function of H2A.Z appears to be essential in a number of organisms, including F. fujikuroi and F. graminearum (Sevilla and Binda 2014 ; Chen et al 2020 ).…”
Section: Advances In the Molecular Regulation Of The Biosynthesis Of ...mentioning
confidence: 99%
“…For Fusarium ssp., genetic differentiation of the population structure of races was reported. In particular, the occurrence of specific pathotypes was found [34][35][36][37]. Another paper reported the biological, physiological, and pathogenic differentiation of a genetically homogeneous population of F. oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 98%
“…The genetic diversity of organisms is significantly increased by mutations. It was found that Fusarium is also subject to mutagenesis [34,35].…”
Section: Discussionmentioning
confidence: 99%